2017
DOI: 10.1259/bjr.20170110
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between obesity and fat-infiltrated axillary lymph nodes visualized on mammography

Abstract: We found a highly significant association between increasing BMI and axillary LN dimensions independent of age and breast density with strong interobserver agreement. The increase in LN size was driven by expansion of the LN hilum secondary to fat infiltration. Advances in knowledge: This preliminary work determined a relationship between fat infiltrated axillary lymph nodes and obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…We found that enlarged fat expanded axillary lymph nodes were strongly associated with node-positive breast cancer in obese women despite age, BMI, and tumor characteristics. Previous studies have shown that obesity is associated with an increased size of axillary LNs due to hilar fat expansion without associated increase in cortical size, a finding demonstrated by increased hilo-cortical ratio in enlarged nodes of obese women [ 10 ]. This morphology is in contrast to the diffuse cortical thickening seen with reactive adenopathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that enlarged fat expanded axillary lymph nodes were strongly associated with node-positive breast cancer in obese women despite age, BMI, and tumor characteristics. Previous studies have shown that obesity is associated with an increased size of axillary LNs due to hilar fat expansion without associated increase in cortical size, a finding demonstrated by increased hilo-cortical ratio in enlarged nodes of obese women [ 10 ]. This morphology is in contrast to the diffuse cortical thickening seen with reactive adenopathy.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3 . Analysis of lymph node measurements visualized mammographically in the contralateral axilla is available in the Supplementary Material and measured as described in the prior study [ 10 ]. In order to avoid potential inclusion of morphologically normal nodes with micro-metastases occult to imaging in the ipsilateral axilla, we did not include measurements of ipsilateral axillary lymph nodes on MRI or mammography in the primary analysis, but they are available in the Supplementary Materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The single largest LN within the axilla was chosen as the index node and measured along its greatest longitudinal axis in the axial or sagittal plane as shown in Figure 2 and Figure 3 . Analysis of lymph node measurements visualized mammographically in the contralateral axilla is available in the Supplementary Material and measured as described in the prior study [10]. In order to avoid potential inclusion of morphologically normal nodes with micro-metastases occult to imaging in the ipsilateral axilla, we did not include measurements of ipsilateral axillary lymph nodes on MRI or mammography in the primary analysis, but they are available in the Supplementary Materials .…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have found that obesity is associated with enlarged axillary LNs on screening mammograms secondary to fat expansion of the radiolucent LN hilum without accompanying enlargement of the nodal cortex as demonstrated in Figure 1(b) [10, 11]. There is marked variability in the degree of fatty node enlargement among obese women with similar body mass index (BMI), yet the clinical significance of this variability is unknown ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%